A therapeutic regimen for 3-hydroxyisobutyryl-CoA hydrolase deficiency with exercise-induced dystonia. (September 2019) - Xu, Yan; Zhang, Jing; Yu, Kang; Feng, Feng; Sun, Xiayuan; Li, Chunwei; Li, Huili; Cui, Liying
Abstract: 3-Hydroxyisobutyryl-CoA hydrolase (HIBCH) deficiency is a recently described disease resulting from mutations in HIBCH with no effective treatment. Here, we report a female Chinese patient presenting with exercise-induced dystonia and bilateral symmetrical hyperintensities of the globus pallidus on brain MRI associated with novel HIBCH mutations (c.1027C>G;p. H343D and c.383T>A;p.V128D). After treatment for 1 year with a low-valine diet, both clinical symptoms and brain lesions improved substantially. We propose that HIBCH deficiency should be considered in the differential diagnosis for patients with exercise-induced dystonia, particularly if bilateral symmetrical lesions in the globus pallidus are present. A low-valine diet is a potentially promising treatment for HIBCH deficiency. Highlights: Different diagnosis of HIBCH deficiency with exercise-induced dystonia, bilateral symmetrical lesions in the globus pallidus. A low-valine diet is a potentially promising therapy for HIBCH deficiency. A compound heterozygouse mutations in HIBCH cause HIBCH deficiency.